POLYMORPHISM OF C825T (RS5443) G-PROTEIN 3-SUBUNIT GENE AND THE LONG-TERM PROGNOSIS FOR PATIENTS WITH HEART FAILURE - Pyvovar, S.M.; Rudyk, Yu.S.; Lozyk, T.V.; Galchinska, V.Yu. (World of Medicine and Biology, 2019)
Forecasting of an unfavorable course in heart failure is very relevant. The purpose of the work was to determine the effect of the G protein β3-subunit C825T (RS5443) gene polymorphism on the long-term prognosis for patients with heart failure. The study included 170 patients with heart failure on the background of post-infarction cardiosclerosis. The G protein β3-subunit C825T (RS5443) gene polymorphism was determined by means of the polymerase chain reaction. Daily monitoring of ECG, Doppler echocardioscopy were carried out. The observation period was 3 years, whereby the course of the disease was evaluated, the atrial fibrillation paroxysms development, the frequency of hospitalizations due to the disease decompensation, and mortality were taken into account. The frequencies of the C825T (RS5443) polymorphic variants of the G protein β3-subunit gene were determined in the patients. 47% of patients are homozygous carriers of C825 alleles, 47% of patients are heterozygotes (C825T), 11 out of 170 patients are homozygous by the T genome. Homozygous patients with T genome are younger by 7.5 years, compared to homozygous C-allele patients and by 6 years younger compared to heterozygotes (CT) (p
Keywords: heart failure; clinical course; atrial fibrillation; C825T (RS5443) polymorphism; gene; β3 subunit of G protein